The teeth of the ILO : the impact of the 1998 ILO Declaration on Fundamentals Principles and Rights at Work - Kari, Tapiola; International Labour Organization (Geneva International Labour Organization (ILO), 2018)
This book explains how the ILO faced the challenges of globalization to social and labour rights when the end of the Cold War and new information technology changed the practice of international economic relations and trade. It traces the reaction to the continued use of child and forced labour, discrimination and denial of trade union rights. The result was the 1998 Declaration of the ILO on Fundamental Principles and Rights at Work. The ratification of the ILO Conventions on these rights has reached record levels.
1. The declarations of the ILO -- 2. Two centuries of labour rights -- 3. Six years of negotiation -- 4. Making the Declaration work -- 5. Shifting realities and perceptions -- 6. Making use of teeth on the ground -- 7. Twenty years later -- 8. Epilogue: The big picture
Keywords: International law; INTERNATIONAL AGREEMENTS; LABOUR; WORKERS; HUMAN RIGHTS